Waist circumference as a predictor for blood glucose levels among men and women 40 to 60 years of age - Hardiman, Shinta L; Nevita, Intan; Krisna, Puspa; Susiyanti, Eva (Universa Medicina, 2008)
Anthropometric indexes such as body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist hip ratio (WHR), are useful measurements to provide important information on blood glucose concentration. The aim of this study was to determine several anthropometric measurements, in particular BMI, WC, HC and WHR, in their ability to predict the blood glucose levels in men and women 40 to 60 years of age. A cross-sectional study was conducted on 44 men and 127 women aged 40 to 60 who lived in Cipete Selatan subdistrict, South Jakarta. Blood glucose levels were assessed and anthropometric indexes such as BMI, WC, HC, WHR were measured. Multiple linear regression analysis was used to determine the best predictor for blood glucose levels. The study showed that the prevalence of diabetes mellitus (DM) type 2 was 12.9% and higher in men (20.5%) than in women (10.2 %). The significant predictive variables in the simple regression analysis were age and WC. Multiple linear regression showed that after adjustment for age, WC was positively associated with blood glucose levels. Standardized b value was 0.172 (p=0.026). WC predicts blood glucose levels, beyond that explained by traditional diabetic risk factors and BMI. The findings support the recommendation that WC be a routine measure for identification of DM type 2 in men and women aged 40 to 60.